'I take for granted that patients know' – oral health professionals' strategies, considerations and methods when teaching patients how to use fluoride toothpaste. Issue 2 (11th July 2013) - Jensen, O; Gabre, P; Sköld, UM; Birkhed, D; Povlsen, L
Abstract Objectives The aim of this study was to explore the oral health professionals' (OHPs') perspectives regarding their strategies, considerations and methods when teaching their patients the most effective way of toothbrushing with fluoride (F) toothpaste. Methods A qualitative research method was used to collect data. To stimulate interactivity among the participants, interviews were performed in focus groups. Five groups of OHPs, including dentists, dental hygienists and dental nurses, were interviewed a total of 23 individuals. The interviews were analysed using manifest and latent qualitative content analysis. Data were systematically condensed and coded to the relevant phrases that identified their content. Results Three categories were identified in the manifest and latent content analysis: (i) strategies and intentions, (ii) providing oral hygiene information and instruction and (iii) barriers to optimal oral healthcare education. Health promotion and seeing to the patients' best interest were driving forces among the OHPs as well as personal success in their preventive work. They focused on toothbrushing techniques more than on how to use F toothpaste. Barriers to oral health information were cost to the patients and, to some extent, the opinion of the OHPs that some patients were impossible to motivate or that patients already know what to do. Conclusion The OHPs described toothbrushing with F toothpaste as very important, although the plaque removal perspective dominated. They did not focus on how to use F toothpaste, because they believed that knowledge about and appropriate behaviour concerning F toothpaste were already familiar to their patients.